4x-3x-x=x-5

Simple and best practice solution for 4x-3x-x=x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3x-x=x-5 equation:


Simplifying
4x + -3x + -1x = x + -5

Combine like terms: 4x + -3x = 1x
1x + -1x = x + -5

Combine like terms: 1x + -1x = 0
0 = x + -5

Reorder the terms:
0 = -5 + x

Solving
0 = -5 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
0 + -1x = -5 + x + -1x
Remove the zero:
-1x = -5 + x + -1x

Combine like terms: x + -1x = 0
-1x = -5 + 0
-1x = -5

Divide each side by '-1'.
x = 5

Simplifying
x = 5

See similar equations:

| (3x-8)(4x-9)=0 | | 13p-3=4209 | | 4a^2-2a/2a-1 | | 3v^2=-3 | | e^4x=12+e^2x | | ((5)/(8))-((x-3)/(5))=((3x)/(10)) | | Cot(x)=0.5 | | x*6+88=x*10-12 | | (X+7)3=45 | | X^2-2=19 | | 70/250 | | 24d^2+39d-18= | | (1/x-5)^2-(x-5)^2 | | 11x+18=8x-6 | | (16x+2x)(8+2x)=0 | | 13=n*2-3n | | 2x+22x+56= | | 36x^5-12x^4-44x^3+12x^2+12x-31=0 | | (24+2x)(12+2x)=0 | | X^2-14x-70=0 | | (4x-5)(8x+9)=0 | | x/6=x/2-3 | | 4(x+4)-2=-1 | | 8t-10-10t+15= | | -18x^5-14x^3-2x+1=0 | | d/-14=3 | | -48=6b+6 | | 5+22k=16 | | 3(x+2)+2(x-4)=x-3(x-3) | | (17x+6)-(7x-2)=39 | | d/-5=-7 | | 2x+8=6x+14 |

Equations solver categories